2015
DOI: 10.1007/s12035-015-9239-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations of Kinase Inserts Domain Receptor (KDR) Gene Are Associated with the Risk of Astrocytomas

Abstract: Astrocytomas is one of the most common central nervous system (CNS) tumors with high mortality rate. Kinase insert domain receptor (KDR) is involved in the regulation of tumor angiogenesis, migration, and vascular permeability. The aim of the study was to explore the relationship between KDR polymorphisms and risk of astrocytomas. Blood samples were collected from 157 astrocytomas patients and 160 healthy controls. Three tag-SNPs (rs2071559C/T, rs2305948T/C, and rs1870377A/T) were identified from the Internati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Moreover, Q472H mutation was found to increase KDR protein phosphorylation and associated with MVD in non-small cell lung cancer [ 33 ]. However, this mutation in astrocytomas showed a protective effect [ 34 ]. In ES, it has been shown that VEGF plays an important role in angiogenesis and tumorigenesis, but the mechanism involving its receptors is not clear [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Q472H mutation was found to increase KDR protein phosphorylation and associated with MVD in non-small cell lung cancer [ 33 ]. However, this mutation in astrocytomas showed a protective effect [ 34 ]. In ES, it has been shown that VEGF plays an important role in angiogenesis and tumorigenesis, but the mechanism involving its receptors is not clear [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the frequent presence of the variant in our patient cohort the allele frequency did not significantly differ from the general population suggesting a limited impact on oncogenesis. 32,33 However, the KDR (kinase insert domain receptor, also known as VEGFR2) Q472H variant has been associated with an angiogenic phenotype characterized by increased tumor vascular density and VEGF secretion. Studies on melanoma cells harboring KDR Q472H demonstrated higher proliferative and invasive capacity and sensitivity to targeted inhibition of VGFR2.…”
Section: Discussionmentioning
confidence: 99%
“…Some gene polymorphisms are functional and can affect the expression or structure of a protein [41,42]. In the VEGF and VEGFR2 genes, we focused on four functional VEGF polymorphisms (2549 I/D, rs1570360 G/A, rs2010963 C/G, and rs3025039 C/T) and two functional VEGFR2 polymorphisms (rs2071559 C/T and rs1870377 A/T), which may affect angiogenesis-related diseases [43][44][45][46][47][48][49][50][51].…”
mentioning
confidence: 99%
“…The rs1870377 A/T polymorphism changes the sequence of the amino acids from His (T allele) to Gln (A allele), and the T allele shows higher binding affinity of VEGF to VEGFR2 [50]. This allele is also associated with susceptibility to astrocytomas [51].…”
mentioning
confidence: 99%